2018
DOI: 10.3389/fpsyg.2018.00563
|View full text |Cite
|
Sign up to set email alerts
|

Leaders’ Expressed Humility and Followers’ Feedback Seeking: The Mediating Effects of Perceived Image Cost and Moderating Effects of Power Distance Orientation

Abstract: We developed and tested a model to identify the role of leaders’ expressed humility on employees’ feedback-seeking processes. The data used in our study was from a sample of 248 employees and 57 of their immediate supervisors. The results revealed that: (1) leader’s expressed humility positively related to employees’ feedback seeking mediated by employees’ perceived image cost; and (2) power distance orientation moderated the relationship between leader’s expressed humility and employees’ perceived image costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…What is also worth noting is that one limitation of this study is that we reported small effect sizes of follower competence on leader humility expression, which raises the question of whether these effects have meaningful implications for practice in management. The answer to this question is “yes.” Firstly, our small effect sizes are comparable to some previous studies of leader humility (Qian et al, 2018). Secondly, despite the small sizes, we obtain such effects after ruling out the influence of leaders’ humility trait.…”
Section: Discussionsupporting
confidence: 89%
“…What is also worth noting is that one limitation of this study is that we reported small effect sizes of follower competence on leader humility expression, which raises the question of whether these effects have meaningful implications for practice in management. The answer to this question is “yes.” Firstly, our small effect sizes are comparable to some previous studies of leader humility (Qian et al, 2018). Secondly, despite the small sizes, we obtain such effects after ruling out the influence of leaders’ humility trait.…”
Section: Discussionsupporting
confidence: 89%
“…Leadership substantially influences the work lives of employees (Qian et al, 2018) and can be viewed as an important social context/situational factor that affects employee responses in the workplace (e.g., Williams et al, 2010; Nguyen et al, 2016; Wang et al, 2018a). Social context is “an integral ingredient enabling the kinds of mental models that lead to resilience” (Lengnick-Hall et al, 2011, p. 247; also see Cooper et al, 2019, p. 89).…”
Section: Introductionmentioning
confidence: 99%
“…Leaders who show humility are more concerned with the interests of others than their own interests, hence they will be able to elicit a transformational leadership style which leads to the growth of respect, trust, and creativity from their employees (Morris, et al, 2005). Leader humility have been demonstrated to bring out employee behaviors that improve productivity such as voice behavior, feedback seeking, organizational citizenship behavior, and team creativity (Hu, et al, 2018;Jeung & Yoon, 2016;Lin, et al, 2019;Qian, et al, 2018;Qian, et al, 2020;Yang, et al, 2019;Zhong, et al, 2020).…”
Section: Leader Humilitymentioning
confidence: 99%